Formulasi Dan Stabilitas Fisik Krim Ekstrak Daun Kelor (Moringa Oleifera Lamk) Dengan Perbedaan Humektan - Yuliana, Tiara Hendry; Puradewa, Levi; Nurcahyani, Diah (Jompa Research and Development, 2023)
One of the medicinal plants used as traditional medicine is kelor (Moringa oleifera Lamk). Moringa leaves are rich in vitamin C and antioxidants which can increase collagen production to prevent and slow down premature aging. The effect of humectants on cream preparations is to obtain creams that have good physical characteristics during storage. This study aims to determine the formulation and physical stability of moringa leaf extract cream preparations (Moringa oliefera Lamk) that meet the requirements. The variations of humectants used in this study include propylenglycol-glycerin (FI), glycerin (FII) and propylenglycol (FIII). Stearic acid, cetyl alcohol (oil phase) were melted on a water bath, TEA, methylparaben, propylparaben, glycerol and distilled water (water phase) were heated. The two phases gradually and grind to form a creamy mass and add the extract. Test the physical quality of the cream for 1 week, namely organoleptic test, homogeneity test, pH test, spreadability test and viscosity test. The results of the cream spreadability test of Moringa leaf extract (Moringa oleifera Lamk) in formula I did not meet the requirements, formula II produced cream preparations that met the requirements with a spreadability range of 5-6 cm, formula III did not meet the requirements. The results of the viscosity test on the formula I, II, III are in the range of 22000-30000 cPs. Based on the results of research on formula II with the addition of the humectant glycerin, it produces a good cream preparation.